Edukasi Perencanaan Keuangan Sejak Dini Dalam Membangun Generasi Ekonomi Muda Yang Mandiri - Bakti, Surya; Suriono, Hadi; Optari, Leni Kurnia; Dewantoro, Riy (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
The rapid advancement of the times demands that the younger generation possess strong financial literacy to face economic challenges and a consumptive lifestyle. However, the financial literacy level among Indonesian students remains low, affecting their ability to manage personal finances. This community service activity was conducted at SMA Swasta Nasional Petatal, Batubara Regency, North Sumatra, on 18 July 2025, aiming to enhance students’ understanding and foster healthy financial habits from an early age. The implementation method included preparation, interactive education, and evaluation. The materials covered pocket money management, basic Budgeting, distinguishing needs from wants, and the introduction of saving and investment concepts. The results showed a significant improvement in students’ understanding based on pre-test and post-test scores, along with increased awareness and motivation to manage finances wisely. Active participation and positive feedback served as indicators of the program’s success. This activity underscores the importance of integrating financial literacy into secondary education to shape a generation that is independent, responsible, and prepared to face future economic challenges.